Intra-Articular Injection of (−)-Epigallocatechin 3-Gallate (EGCG) Ameliorates Cartilage Degeneration in Guinea Pigs with Spontaneous Osteoarthritis - Hsuan-Ti Huang; Tsung-Lin Cheng; Chung-Da Yang; Chi-Fen Chang; Cheng-Jung Ho; Shu-Chun Chuang; Jhong-You Li; Shih-Hao Huang; Yi-Shan Lin; Hsin-Yi Shen; Tsung-Han Yu; Lin Kang; et al. (MDPI AG, 2021)
Osteoarthritis (OA) is the most prevalent joint disease that causes an enormous burden of disease worldwide. (−)-Epigallocatechin 3-gallate (EGCG) has been reported to reduce post-traumatic OA progression through its anti-inflammatory property. Aging is the most crucial risk factor of OA, and the majority of OA incidences are related to age and not trauma. In this study, we assess whether EGCG can ameliorate cartilage degradation in primary OA. In an in-vitro study, real-time PCR was performed to assess the expression of genes associated with human articular chondrocyte homeostasis. A spontaneously occurring OA model in guinea pigs was used to investigate the effect of EGCG in vivo. OA severity was evaluated using Safranin O staining and Osteoarthritis Research Society International (OARSI) scores, as well as by immunohistochemical (IHC) analysis to determine the protein level of type II collagen (Col II), matrix metalloproteinase 13 (MMP-13), and p16 ink4a in articular cartilage. In the in-vitro study, EGCG increased the gene expression of aggrecan and Col II and decreased the expression of interleukin-1, cyclooxygenase 2, MMP-13, alkaline phosphatase, Col X, and p16 Ink4a; EGCG treatment also attenuated the degraded cartilage with a lower OARSI score. Meanwhile, IHC results showed that EGCG exerted an anti-OA effect by reducing ECM degradation, cartilage inflammation, and cell senescence with a less-immunostained Col II, MMP-13, and p16 Ink4a. In conclusion, these findings suggest that EGCG may be a potential disease-modifying OA drug for the treatment of primary OA.